Synergistic effect of feed additives on cell proliferation and morphology in quail (Coturnix coturnix Japonica) duodenum - Asmaz, D E; Yesilbag, D; Odabasi, F; Zık, B (Journal of the Hellenic Veterinary Medical Society, 2022)
The present study aimed to investigate the effect of a commercial probiotic and a commercial essential oil blend and their mixture, as a natural feed additive, on the expression level of Proliferating Cell Nuclear Antigen (PCNA), proliferation index (PI), and total mucosal thickness of quails. 1-day-old Japanese (Coturnix coturnix japonica) quails, including both males and females, were divided into four groups as follows: (1) control treatment without medication (n: 15); (2) 18 g/ ton-1 probiotic (n: 15); (3) 300 g/ ton-1 essential oil blend (n: 15) and (4) 18 g/ ton-1 probiotic plus 300 g/ ton-1 essential oil blend (n: 15). In the study, the effect of natural feed additives added to the quail diet on intestinal health was evaluated by immunohistochemical and histological analyzes. At the end of the experiment, the quail’s duodenum was removed, fixed in 10% neutral buffered formalin, and a histological examination procedure was performed. As a result of the study, it was determined that the PCNA expressions, proliferation index, and mucosal thickness were generally significantly increased in the experimental groups compared to the control group (p<0.001). The combination of additives caused a synergistic effect for this study. All data were statistically significant in the group where the probiotic and essential oil mixture was used together. It has been determined that these feed additives combination stimulates cell proliferation in the duodenum, where nutrients absorbed, and positively affect intestinal morphology.